The Effect of Leadership, Compensation and Competency on Employee Performance - Sarboini, Sarboini; Rizal, Syamsul; Surya, Jen; Yusuf, Zulfan (SCAD Independent, 2018)
This study is an implicit study of the influence of leadership, compensation and competence on employee performance of Banda Aceh Public Health Office. The purpose of this research is to know the influence of leadership, compensation and competency either partially or simultaneously on employee performance of Banda Aceh Public Health Office. The study population is all over Government Employees that works on Banda Aceh Public Health Office, amounting to 84 employees. The entire population is sampled because the population is affordable or less than 100. Data collection is done by distributing questionnaires (questionnaires). Primary data are then analyzed by using multiple linear regressions. The results of the study explain the leadership significantly influences the performance of employees in the Public Health Office of Banda Aceh. Compensation has a significant effect on employee performance of Banda Aceh Public Health Office. Simultaneously leadership, compensation and competence have a strong and positive relationship with employee performance at Banda Aceh Public Health Office. The role of leadership, compensation and competence in influencing employee performance at Banda Aceh Public Health Office also more dominant than other variables outside the model.